ANALISIS PENERAPAN ETIKA KEILMUAN DALAM PENULISAN KARYA ILMIAH MAHASISWA - Silvia, Nela; Susanto, Edi; Parizal; Juniarti, Vevi; Annisa, Siti; Feni Yulianti; Ningsih, Retno Wahyu (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Scientific ethics serves as a fundamental foundation for maintaining academic integrity and improving the quality of students' scientific writing. The rapid development of digital technology, particularly Artificial Intelligence (AI), has created both opportunities and challenges in the implementation of scientific ethics throughout the academic writing process. This study aims to analyze the implementation of scientific ethics in students' scientific writing. The study employed a descriptive qualitative approach. Data were collected through semi-structured interviews with three university students selected using purposive sampling. Data were analyzed using the interactive model of Miles, Huberman, and Saldaña, consisting of data condensation, data display, and conclusion drawing. The findings reveal that the participants demonstrate a good understanding of scientific ethics, reflected in their commitment to academic honesty, proper citation practices, respect for intellectual property rights, and avoidance of plagiarism. AI is perceived as an ethical supporting tool provided that it does not replace students' critical thinking, analytical processes, and academic responsibility. The implementation of scientific ethics is supported by lecturers' guidance, academic writing training, access to credible references, and the use of reference management software. However, limited information literacy, restricted access to scholarly journals, and insufficient understanding of citation techniques remain significant challenges. This study concludes that strengthening academic integrity through scientific ethics education, improving academic literacy, and establishing clear guidelines for the responsible use of AI are essential to enhancing the quality of students' scientific writing.